Cho $\frac{1}{a}$+ $\frac{1}{b}$ +$\frac{1}{c}$ = 2 và $\frac{1}{a^{2} }$ + $\frac{1}{b^{2}}$ + $\frac{1}{c^{2}}$ =2 ( abc$\neq$ 0). Chứng minh rằng a+b+c=abc
Cho $\frac{1}{a}$+ $\frac{1}{b}$ +$\frac{1}{c}$ = 2 và $\frac{1}{a^{2} }$ + $\frac{1}{b^{2}}$ + $\frac{1}{c^{2}}$ =2 ( abc$\neq$ 0). Chứng minh rằng a+b+c=abc
Ta có $\frac{1}{a}$ +$\frac{1}{b}$ +$\frac{1}{c}$=2
⇒ ( $\frac{1}{a}$ +$\frac{1}{b}$ +$\frac{1}{c}$ )²=2²
⇒ $\frac{1}{a^{2} }$+$\frac{1}{b^{2} }$+ $\frac{1}{c^{2} }$ + 2($\frac{1}{ab}$+ $\frac{1}{ac}$+ $\frac{1}{bc}$)=4
⇒ 2 + 2($\frac{c}{abc}$+ $\frac{b}{abc}$+ $\frac{a}{abc}$)=4
⇒ 2( $\frac{a+b+c}{abc}$)=2
⇒ $\frac{a+b+c}{abc}$=1
⇒ a+b+c=abc
Vậy a+b+c=abc (đpcm)
Học tốt…
Giải thích các bước giải:
$\begin{array}{l}
\frac{1}{a} + \frac{1}{b} + \frac{1}{c} = 2\\
= > {\left( {\frac{1}{a} + \frac{1}{b} + \frac{1}{c}} \right)^2} = 4\\
< = > \frac{1}{{{a^2}}} + \frac{1}{{{b^2}}} + \frac{1}{{{c^2}}} + 2\left( {\frac{1}{{ab}} + \frac{1}{{bc}} + \frac{1}{{ca}}} \right) = 4\\
< = > 2 + 2\left( {\frac{1}{{ab}} + \frac{1}{{bc}} + \frac{1}{{ca}}} \right) = 4\\
< = > \left( {\frac{1}{{ab}} + \frac{1}{{bc}} + \frac{1}{{ca}}} \right) = 1\\
< = > \frac{{a + b + c}}{{a.b.c}} = 1\\
= > a + b + c = abc
\end{array}$